WAYS TO IMPROVE FINANCIAL AND CREDIT MECHANISMS FOR SUPPORTING ENTERPRISES IN THE REGIONS (Academicia Globe: Inderscience Research, 2023)
This article aims to study ways to improve financial and credit mechanisms for supporting enterprises in regional conditions. It emphasized the importance of effective financial and credit systems in promoting economic development, encouraging entrepreneurship, and increasing the competitiveness of enterprises in different regions. The topic examines the challenges faced by businesses in accessing financial resources, particularly in underdeveloped or remote areas, and potential solutions that can be implemented to overcome these challenges. It emphasizes the need for adapted financial and credit mechanisms, taking into account the specific needs and characteristics of enterprises operating in different regional conditions. The abstract also discusses the role of public policy, financial institutions, and public-private partnerships in creating an enabling environment for enterprise development at the regional level. Overall, the report emphasizes the importance of continued efforts to improve financial and credit mechanisms to support businesses and stimulate regional economic growth.